Research of composite safety protection for digital maps - Feng XU; Jia-nan LI; Jian-guo SUN (Tongxin xuebao)
An adaptive watermarking technology for 2D electronic charts was proposed. It took count in the discrete wavelet domain scheme, and obtained an ideal embedding set for watermarks in the electronic chart space. In order to preserve topology of map effectly by the large embedding rates and protect the safety of watermarking scenario, a gray balance means was provided, and the maximum capacity in each divided rectangle blocks in the electronic charts was computed.The experiment also shows that it can adapt to data perturbation by conventional operations.The method has better robustness.